From Philosophy to Praxis: Managing the Living Qur’an, BTQ Program and Policy Urgency in Islamic Higher Education - Moh. Zainal Fanani; Mubaidi Sulaeman (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the management of the Baca Tulis al-Qur’an (BTQ-Read and Write Qur’an) program as a practical implementation of the Living Qur’an approach in Islamic higher education, with a particular focus on its contribution to bridging the gap between philosophical discourse and institutional praxis. While existing Living Qur’an studies are often dominated by symbolic and theoretical discussions, the managerial and applicative dimensions within State Islamic Religious Universities remain underexplored. The research employs a qualitative case study method at the State Islamic Institute (IAIN) Kediri, involving in-depth interviews with 35 informants, six months of participatory observation, and analysis of 17 institutional documents. This methodological triangulation provides a comprehensive understanding of how BTQ is managed and operationalized. The findings reveal that the BTQ program at IAIN Kediri is organized through a systematic and collaborative management model, featuring a tiered curriculum based on the Jamiati method that adapts to students’ varying competencies. This strategy has demonstrably enhanced Qur’anic literacy, as indicated by the increase in students achieving the advanced category (grade A) from 11.75% in 2020 to 25.74% in 2024. More importantly, the BTQ program functions as a strategic instrument for embodying the Qur’an in academic and spiritual life, transforming it from a text of study into a lived practice shaping values, attitudes, and behavior. Theoretically, this research contributes to Living Qur’an studies by advancing a contextualized model of Qur’anic learning management that integrates institutional policy, pedagogical innovation, and spiritual formation. It highlights the urgency of moving from philosophy to praxis in order to develop sustainable and adaptive frameworks that can inform broader policy and practice in Islamic higher education.